2003
DOI: 10.1034/j.1399-0039.2003.610106.x
|View full text |Cite
|
Sign up to set email alerts
|

TNFA–TNFB haplotypes modify susceptibility to type I diabetes mellitus independently of HLA class II in a Moroccan population

Abstract: The contribution of single nucleotide polymorphisms in tumor necrosis factors (TNF) alpha and beta to autoimmune diseases, and to type 1 diabetes mellitus (T1DM) in particular, is not well established, and may be confounded by linkage disequilibrium to class II HLA genes. At least two polymorphisms seem to have functional relevance in the respective genes: TNFA-307 and TNFB+252. We have typed these two polymporphisms in samples of Moroccan T1DM patients and controls for which class II HLA genes had already bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…However, several other studies found an independent effect of TNF/LTA with T1DM [17][18][19][20]. TNF involvement in the destruction of pancreatic β-cells [10,11] and multiple inflammatory activities of TNF and LTA cytokines make them plausible targets for revealing molecular susceptibility to T1DM.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, several other studies found an independent effect of TNF/LTA with T1DM [17][18][19][20]. TNF involvement in the destruction of pancreatic β-cells [10,11] and multiple inflammatory activities of TNF and LTA cytokines make them plausible targets for revealing molecular susceptibility to T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…TNF involvement in the destruction of pancreatic β-cells [10,11] and multiple inflammatory activities of TNF and LTA cytokines make them plausible targets for revealing molecular susceptibility to T1DM. The joint analysis of TNF and LTA genes may be more informative in defining the risk/protection to T1DM susceptibility [7,18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations